The Advances in Diagnosis and Treatment of Brugada Syndrome: A Comprehensive Review - Szepietowski, Bartosz; Mączyńska, Wiktoria; Dutkiewicz, Justyna; Wijata, Michał; Wijata, Anna Maria; Przybyłek-Stępień, Zuzanna Adriana; Bartosiński, Ryszard; Szustak, Jan; Kąpa, Maria; Kaźmierczak, Jakub Marek; Rycerz, Ewelina; Pasek, Piotr (Quality in Sport, 2025)
Introduction: Brugada Syndrome (BrS) is a rare genetic cardiac disorder that predisposes individuals to ventricular fibrillation and sudden cardiac death, often without structural heart disease. The condition, first described in 1992, is characterized by a distinct electrocardiographic (ECG) pattern and remains a diagnostic and therapeutic challenge. Aim of the Study: This review aims to evaluate current literature on BrS, focusing on diagnostic criteria, risk stratification, and treatment options. By analyzing recent findings from electrophysiological studies, genetic research, and clinical trials, the study seeks to provide a comprehensive understanding of the syndrome and its management. Materials and Methods: The literature available in the PubMed database was reviewed using the following keywords: "Brugada Syndrome," "Brugada Syndrome diagnosis," "Brugada Syndrome treatment," "risk stratification in Brugada Syndrome," "sudden cardiac death and Brugada Syndrome," and "electrocardiographic patterns in Brugada Syndrome." Conclusion: Brugada Syndrome remains a complex condition with ongoing challenges in risk stratification and treatment optimization. While ICDs are the primary intervention for high-risk patients, their use in asymptomatic individuals remains controversial. Pharmacological therapies and catheter ablation provide alternative treatment options but require further validation. Advances in genetic testing, electrophysiological studies, and noninvasive diagnostic tools hold promise for improving risk assessment and treatment precision. Future research should focus on refining risk prediction models and enhancing personalized therapeutic strategies. Keywords: Brugada Syndrome, sudden cardiac death, electrocardiography, risk stratification, implantable cardioverter-defibrillator, pharmacological therapy, catheter ablation